Effect of soil fertility on host response to black leaf streak of plantain (Musa spp. AAB group) under traditional farming systems in southwestern Nigeria - Mobambo, K.N.; Zuofa, K.E.; Gauhl, F.; Adeniji, M.; Pasberg-Gauhl, C. (Informa UK Limited, 1994)
Plantain (Musa spp., AAB group) is a staple food crop in the humid forest regions of West and Central Africa. Its cultivation is threatened by black leaf streak (BLS), an air‐borne fungal leaf spot disease, caused by Mycosphaerella fijiensis Morelet. An on‐farm survey for BLS severity in relation to soil fertility was conducted in two different geomorphological zones, the main plantain‐growing areas of Rivers State where plantain is mostly cultivated in compound gardens and in outlying fields mixed with other food crops. Plantain in the Meander belts zone (the Central Niger Delta area) was less infected by BLS than in the Coastal plain sands (the east of the Niger delta). In addition, plantain grown in homestead gardens had a much lower BLS severity than that planted in field‐plots. The host plant response is attributable to the difference in soil fertility both between the two geomorphological zones and between the two farming systems. Therefore, the success of a system would depend on managing the soil in a way that fertility is maintained. Since chemical fertilizers are not readily and economically available to the farmers, the potential of traditional organic fertilizers needs to be better exploited.